2012
DOI: 10.5194/amt-5-397-2012
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of CH<sub>4</sub>, HDO, H<sub>2</sub>O, and N<sub>2</sub>O with improved lower tropospheric vertical resolution from Aura TES radiances

Abstract: Abstract. Thermal infrared (IR) radiances measured near 8 microns contain information about the vertical distribution of water vapor (H 2 O), the water isotopologue HDO, and methane (CH 4 ), key gases in the water and carbon cycles. Previous versions (Version 4 or less) of the TES profile retrieval algorithm used a "spectral-window" approach to minimize uncertainty from interfering species at the expense of reduced vertical resolution and sensitivity. In this manuscript we document changes to the vertical reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 55 publications
3
182
0
Order By: Relevance
“…A new generation of instruments has been launched on polar platforms satellites, such as Interferometric Monitor for Greenhouse gases (IMG, e.g., Ogawa et al, 1994;Clerbaux et al, 1998), Tropospheric Emission Spectrometer (TES, e.g., Shephard et al, 2008;Worden et al, 2012), the Advanced Infrared Sounder (AIRS, Chahine et al, 1990;Aumann and Miller, 1995), and the Infrared Atmospheric Sounding Interferometer (IASI, e.g., Clerbaux et al, 2009;Hilton et al, 2012). Thanks to a larger number of spectral channels and an enhanced spectral resolution, these instruments lead to improved vertical resolutions down to 1 km and higher precision of both the atmospheric temperature and water vapor content retrieval.…”
Section: P Chazette Et Al: Comparison Of Iasi Water Vapor Retrievalmentioning
confidence: 99%
“…A new generation of instruments has been launched on polar platforms satellites, such as Interferometric Monitor for Greenhouse gases (IMG, e.g., Ogawa et al, 1994;Clerbaux et al, 1998), Tropospheric Emission Spectrometer (TES, e.g., Shephard et al, 2008;Worden et al, 2012), the Advanced Infrared Sounder (AIRS, Chahine et al, 1990;Aumann and Miller, 1995), and the Infrared Atmospheric Sounding Interferometer (IASI, e.g., Clerbaux et al, 2009;Hilton et al, 2012). Thanks to a larger number of spectral channels and an enhanced spectral resolution, these instruments lead to improved vertical resolutions down to 1 km and higher precision of both the atmospheric temperature and water vapor content retrieval.…”
Section: P Chazette Et Al: Comparison Of Iasi Water Vapor Retrievalmentioning
confidence: 99%
“…Because of a limited number of in situ measurements in time and space domain, the quantification of CH 4 emissions from different sources and in different regions still remains largely uncertain. In recent years, space-borne measurements of CH 4 from satellites have become available, such as the measurements using the thermal infrared (TIR) sensors, which include the Atmospheric InfraRed Sounder (AIRS) on NASA/Aqua (Aumann et al, 2003;Xiong et al, 2008Xiong et al, , 2010a, the Tropospheric Emission Spectrometer (TES) on NASA/Aura (Payne et al, 2009;Wecht et al, 2012;Worden et al, 2012), and the Infrared Atmospheric Sounding Interferometer (IASI) on METOP-A and METOP-B (Xiong et al, 2013;Crevoisiter et al, 2009Crevoisiter et al, , 2013Razavi et al, 2009). Measurements using the Near-Infrared (NIR) sensors include the SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) instrument onboard ENVISAT for (Frankenberg et al, 2008, and the Thermal And Near infrared Sensor for carbon Observation (TANSO) onboard the Greenhouse gases Observation SATellite (GOSAT) from 2009 to present (Yokota et al, 2009;Paker et al, 2011;Schepers et al, 2012;Saitoh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This method also has the large advantage of minimizing the error on the δD profile (e.g. Schneider et al, 2006) as demonstrated for example by Worden et al (2006Worden et al ( , 2007Worden et al ( , 2012 on TES measurements, on IASI measurements by Schneider and Hase (2011) and Lacour et al (2012), or for ground-based measurements by Schneider et al (2006Schneider et al ( , 2010Schneider et al ( , 2012.…”
Section: Particularity Of the δD Retrieval: The Hdo / H 2 O Correlatementioning
confidence: 99%
“…Prior to IASI, the Interferometric Monitor for Greenhouse gases (IMG) (Zakharov et al, 2004;Herbin et al, 2007) and the Tropospheric Emission Spectrometer (TES) provided quasi-global distributions of δD representative of the mid-troposphere (e.g. Worden et al, 2006Worden et al, , 2007 whereas the SCanning Imaging Absorption spectrometer for Atmospheric CartograpHY (SCIAMACHY) instrument provided total column distributions, with sensitivity down to the boundary layer (Frankenberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%